2021
DOI: 10.1002/pd.5887
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical stem cell therapy in fetuses with myelomeningocele: A systematic review and meta‐analysis

Abstract: Objective We performed a systematic review to summarize the efficacy and safety of in utero stem cells application in preclinical models with myelomeningocele (MMC). Methods The study was registered with PROSPERO (CRD42019160399). We searched MEDLINE, Embase, Web of Science, Scopus and CENTRAL for publications articles on stem cell therapy in animal fetuses with MMC until May 2020. Publication quality was assessed by the SYRCLE's tool. Meta‐analyses were pooled if studies were done in the same animal model pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…[ 25 ] The stem cell therapy alternative, mainly involving stem cells isolated from gestational tissues, have been reported to improve animal survival and guarantee in utero tissue repair in genetically and mechanically induced spina bifida. [ 11 , 26 28 ] Although promising, the inherent risks and hindrances of cell therapy are many and include but are not limited to issues with scalability, cell differentiation abilities and aging, bystander effect which reduces cell potency, number of cells reaching target sites, and therapeutic outcome. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] The stem cell therapy alternative, mainly involving stem cells isolated from gestational tissues, have been reported to improve animal survival and guarantee in utero tissue repair in genetically and mechanically induced spina bifida. [ 11 , 26 28 ] Although promising, the inherent risks and hindrances of cell therapy are many and include but are not limited to issues with scalability, cell differentiation abilities and aging, bystander effect which reduces cell potency, number of cells reaching target sites, and therapeutic outcome. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Kunpalin et al performed a systematic review and meta‐analysis of 26 published studies using cell administration in utero for spina bifida in animal models. The results from this study revealed that intra‐amniotic injection of allogeneic amniotic fluid mesenchymal stem cells is safe and effective in covering myelomeningocele defects in small animals, while transplantation of human placenta mesenchymal stem cells to the spinal cord of fetal lambs is safe and effective in enhancing lower limb motor function [ 46 ]. All of the above animal studies showed that BM-MNCs/MSCs could repair motor and sensory deficiencies by differentiating into neural lineage cells, secreting growth factors, and proliferating blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in an animal model that is prone to preterm birth and premature rupture of membranes after surgery, transamniotic stem cell therapy enhanced postoperative recovery to a greater extent by promoting local tissue regeneration at the surgical site ( 49 ). The use of biological cells or collagen replacement drugs can also reduce the incidence of complications of inclusion body cysts and myelomeningocele surgery ( 50 ), which has implications for the perfection of myelomeningocele surgery.…”
Section: Introductionmentioning
confidence: 99%